A Real‐Time Electrochemical Impedance Analysis for Water‐In‐Oil Emulsions of Bitumen Diluted with Naphtha. Issue 12 (26th March 2018) - Jiang, Qiuyan; Li, Qiuhong; Li, Jiao; Li, Aixiang; Cong, Rimin; Si, Weimeng; Li, Zichuang
Abstract: In this paper, water‐in‐oil (W/O) emulsions of bitumen diluted with naphtha were characterized by a novel impedance technique in real time. Nyquist diagrams of electrochemical impedance spectra obtained for different systems present different spectra. For the system of bitumen in naphtha, only one semi‐circle is observed, and the resistance (RO ) and capacitor (CO ) are connected in parallel. Impedance measurement shows that the conductivity of bitumen results from the conductive components, asphaltenes. For the system containing W/O emulsions, Nyquist diagram is presented in two semicircles with different diameter, indicating different relaxation times corresponding to bitumen in naphtha and W/O emulsions respectively. The RO and CO are in parallel combination and then connect in series with the resistance (RW/O ) and capacitor (CW/O ) of W/O emulsions. The value of RW/O reduces with the decrease of volume fraction of W/O emulsions, which can be used to characterize the stability of emulsions. At the same time, the impedance spectra analysis plays an important role in the study of demulsification of W/O emulsions by comparing the RW/O after adding demulsifier ethylcellulose (EC). With the increase of EC concentration, the RW/O reduces and eventually disappears due to the decrease of volume fraction of emulsions. Further work needs to be studied to establish the relationship between dielectric constant and volume fraction of emulsions. Abstract : EIS can be used to characterize the diluted bitumen and W/O emulsions of bitumen diluted with naphtha. The value of RW/O almost remains unchanged for the emulsions with the same volume fraction and different particle size. That is to say, the dominant factor for the change of RW/O is the volume fraction of the emulsions, not the particle size.